Analisis Marketing Mix 7P dalam Peningkatan Minat Nasabah terhadap Produk Tabungan Haji di Bank Syariah Indonesia - Maufur, Miqdam; Putri, Sherlly Oktavia Dwi (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This study aims to analyze the marketing strategy of Tabungan Haji products at Bank Syariah Indonesia KCP Magelang Sudirman, focusing on its effectiveness in increasing customer interest. The research background highlights the substantial financial requirements for Hajj pilgrimage and the need for early financial planning, especially given the long waiting lists. Bank Syariah Indonesia provides Tabungan Haji as a solution to facilitate this need, ensuring financial readiness and fund protection under the supervision of OJK, DPS, and LPS. This qualitative descriptive research employs interviews, observation, and documentation as data collection methods, with data analysis using the Miles, Huberman, and Saldana model. The results indicate that BSI KCP Magelang Sudirman effectively utilizes the 7P marketing mix (Product, Price, Place, Promotion, People, Process, and Physical Evidence) to attract customer interest. The product strategy emphasizes quality, benefits, and flexible Sharia contracts (Wadiah and Mudharabah). The pricing strategy offers affordable initial deposits and minimal balances. The strategic location and digital access enhance convenience. Promotional activities, including socialization and personalized visits, build awareness and trust. Competent and well-trained personnel ensure high-quality service. Streamlined manual and online processes simplify transactions. Finally, comfortable physical evidence, such as well-maintained offices and comprehensive facilities, reinforce credibility. This integrated 7P approach significantly contributes to increasing customer interest and trust in Tabungan Haji products.